PACK-CXL sebagai Terapi Alternatif pada Ulkus Kornea - Pradistya Yudiasari; Angga Fajriansyah (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Corneal ulcer is a leading cause of blindness worldwide. Many of these patients did not respond to conventional treatment with topical agents. Photo Activated Chromophore for Keratitis - Corneal Cross-Linking (PACK-CXL) has been suggested to treat baterial and fungal corneal ulcer that did not respond to antimicrobial agents. Purpose : To report a case series of corneal ulcer treated with PACK-CXL as adjuvant treatment Case Report: Four eyes with corneal ulcer underwent PACK-CXL with ultraviolet-A rays and transepithelial riboflavin according to Dresden procedure. Preoperative and postoperative slit lamp examination of cornea and visual acuity assessment was done. Postoperative outcome includes objective signs like improvement in epithelialization, corneal scarring and vascularization. Result: Three eyes healed completely with scarring at 1-month follow-up. One of the patients developed desematocele in 12 days. Epithelial defect completely healed over time but one underwent amniotic membrane transplant. Responed to treatment were defined by epithelialization and scar formation. Conclusion: The corneal cross-linking has a beneficial role as an adjuvant therapy for corneal ulcer. It helps in relief of pain and healing of ulcer. PACK-CXL can be a choice of adjuvant treatment if the corneal ulcer doesn't heal using topical treatment.